2014 IEEE 40th Photovoltaic Specialist Conference (PVSC) 2014
DOI: 10.1109/pvsc.2014.6925093
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nanostructures and radiation environment on defect levels in III–V solar cells

Abstract: Baseline and quantum dot (QD) GaAs pnjunction diodes were characterized by deep level transient spectroscopy before and after both 1MeV electron irradiation and 140 keV proton irradiation. Prior to irradiation, the addition of quantum dots appeared to have introduced a higher density of defects at E C -0.75 eV. After 1 MeV electron irradiation the wellknown electron defects E3, E4 and E5 were observed in the baseline sample. In the quantum dot sample after 1 MeV electron irradiation, defects near E3, E4 and E … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The performance of solar cells on spacecraft, however, degrades with the irradiation of high-energy particles such as protons and electrons. [7][8][9] Since the performance degradation is caused by the increase in the number of radiation-induced defects, which act as nonradiative recombination (NRR) centers in active layers, the effect of such irradiation on the defect distribution should be clarified. Recently, it has been reported that the PL efficiency of InAs=GaAs QDs enhances from low to intermediate fluences but quenches at higher fluences for InGaAs=GaAs and InAs=GaAs QDs without strain balancing layers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance of solar cells on spacecraft, however, degrades with the irradiation of high-energy particles such as protons and electrons. [7][8][9] Since the performance degradation is caused by the increase in the number of radiation-induced defects, which act as nonradiative recombination (NRR) centers in active layers, the effect of such irradiation on the defect distribution should be clarified. Recently, it has been reported that the PL efficiency of InAs=GaAs QDs enhances from low to intermediate fluences but quenches at higher fluences for InGaAs=GaAs and InAs=GaAs QDs without strain balancing layers.…”
Section: Introductionmentioning
confidence: 99%
“…8,10,11) Experimental results on radiation-induced defects in InAs= GaAs QDs are based on the results of deep-level transient spectroscopy (DLTS), including a recent systematic characterization of electron and hole trap levels with a GaP strain balancing layer. 7,9) DLTS requires us to prepare a suitable Schottky contact or an appropriate p-n junction for measurement. Besides DLTS, another complementary study is desirable to reinforce the distribution of native defects as well as irradiation-induced defects in InAs=GaAs QD structures in order to realize high-efficiency IBSCs.…”
Section: Introductionmentioning
confidence: 99%